DETERMINATION OF ANTIOXIDANTS BY DPPH RADICAL SCAVENGING ACTIVITY OF Limonia acidissima L. FRUIT AND EXOCARP EXTRACTS - Waris, Muhammad Anugerah Alam; Arsyad, Syarifuddin Katjo; Suhendriyo, Suhendriyo (Jurnal Jamu Kusuma, 2025)
Limonia acidissima is one of the medicinal plants in Indonesia with various bioactive compounds that act as an antioxidant. L. acidissima contains alkaloids, flavonoids, and triterpenoids that function as antioxidants. Antioxidants are compounds that help protect the body from damage to cells by free radicals. To determine the antioxidant activity of a plant, one of the most commonly used measurements is through the capture of free radicals using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals. This study has been conducted on the antioxidant activity determination of L. acidissima fruit and exocarp extract with 1,1 Diphenyl-2-picrylhydrazil (DPPH). This study aims to determine the antioxidant activity by observing at the IC50 value contained in the L. acidissima fruit and exocarp extract with DPPH at a wavelength of 478 nm. L. acidissima fruit extract has an IC50 value of 35.190 means antioxidant activity is very strong and L. acidissima exocarp extract has an IC50 value of 35.348 means antioxidant activity is very strong.